MENGEMBANGKAN KETERAMPILAN HIDUP SEHAT MELALUI KURIKULUM SEKOLAH - Ika Zakiah; Aslan Aslan (Jurnal Kesehatan, 2024)
Developing healthy living skills through the school curriculum is an educational approach that aims to integrate health-related knowledge, attitudes and behaviours into the formal learning system. This approach covers various aspects of health, including physical, mental, emotional and social health, which are taught in a systematic and sustainable manner as part of the school curriculum. The aim is to equip students with the practical skills necessary to lead healthy lifestyles and make responsible decisions regarding their health. In this context, healthy life skills include a range of abilities such as an understanding of nutrition and a balanced diet, the importance of physical activity, stress management, communication skills, healthy decision-making, and an understanding of the risks of risky behaviours such as drug use or unsafe sexual behaviour. This approach focuses not only on delivering information, but also on developing practical skills through interactive learning methods, such as group discussions, role plays, and problem-based projects. By integrating healthy living skills into the school curriculum, it is expected that students can develop habits and mindsets that support their health and well-being throughout life.